-6x-6=-5x-2

Simple and best practice solution for -6x-6=-5x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-6=-5x-2 equation:



-6x-6=-5x-2
We move all terms to the left:
-6x-6-(-5x-2)=0
We get rid of parentheses
-6x+5x+2-6=0
We add all the numbers together, and all the variables
-1x-4=0
We move all terms containing x to the left, all other terms to the right
-x=4
x=4/-1
x=-4

See similar equations:

| -3x+24=4(x+2)+2 | | n/2×2+(n-1)1=300 | | 9x+12=2x+89 | | 3(x+1)-7=29 | | 3x+2+x-3+127=180° | | 8x+16=6x+4 | | (x-1)/2+2=2x-2/3 | | 2(2x+4)-4=-4 | | 2^x-1.6=0 | | -4x+21=5(x-5)+10 | | 2x(x+3)+7=0 | | (t+1)²+(t-8)²=4 | | x+(x+6)=8(x+3) | | 2x²-12x+4=18 | | X-5/7x=11 | | 7x+20=6x | | 7x+8=-4x+52 | | 6x=7x+20 | | 4x+35=2x+43 | | 9/4a+7=16 | | (2x)^5=-55 | | y+100=0 | | .2x=10000 | | c/15=22 | | x+4/x-2=x+1/x | | -18x-18x-12=24 | | b/21=-3 | | (6n+2)(5n-8)=0 | | 68=d/4 | | 7(3w+2)/3=-7 | | -2x=-18-8x | | -0.5y=19.5 |

Equations solver categories